Reformulasi Regulasi Radio Komunitas di Indonesia - Yudaninggar, Kartika Sari (POPULIKA, 2019)
Community Radio (CR) in Indonesia has emerged as a media that able to disseminate information to audience. Since this function can not be fullfiled by both private and public radios, CR is important for audience especially for those who lives in remote or even blank spot area. However, Government regulation on CR is feared to deprive the existence of CR. The regulation ranging from limitation of frequency allocation, criteria on coverage area and limited emmitance strength compare to public and private radios.Â  This imply that the Government has never supported the existence of Community Radio. Government and Indonesia Broadcasting Commistion (KPI), as the powerful bodies, ought to reevaluate broadcasting regulation especially on Community Radio. Reformulation on the regulation is needed to maximilize the function of CR in Indonesia as independent media and to support democratization in the broadcasting system in Indonesia.